The Construction of Urban Park Green Infrastructure Network Based on Genetic Algorithm. (25th April 2022) - Wang, Hui; Li, Wei; Hou, Yinfeng; Li, Ma; Lee, Shi-Young
Abstract : In order to build a scientific and reasonable urban park green infrastructure network. Genetic Tabu hybrid algorithm is introduced into the field of urban park green infrastructure network construction, using ENVI5.5, ArcGIS10.2, Conefor2.6, and other software to construct the comprehensive green infrastructure network model and corresponding algorithm of a city park and improve and compare the genetic algorithm and Tabu search algorithm. Firstly, the ecological sensitivity of urban parks was evaluated, and 58 ecological source patches with high ecological value were selected. With the help of GIS platform, 71 potential corridors are simulated and generated by using the minimum cost path model. Then, select the index that can evaluate the importance of source patches in the ecological network to determine the importance ranking of source patches. Finally, according to the principles of clustering and network connectivity, select the ecological source with high patch importance, analyze the potential ecological corridor and current corridor, and combine and screen the factors of green infrastructure network. The results show that a city park green infrastructure network composed of 38 ecological source patches and 19 corridors is finally formed. Genetic algorithm has a potential application prospect in the construction of urban park green infrastructure network. By introducing genetic Tabu hybrid algorithm into the field of urban park green infrastructure network construction, it will change the mode of traditional urban park green infrastructure network construction.